2021
DOI: 10.3390/plants10102160
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Assimilation Related Genes in Brassicanapus: Systematic Characterization and Expression Analysis Identified Hub Genes in Multiple Nutrient Stress Responses

Abstract: Nitrogen (N) is an essential macronutrient for plants. However, little is known about the molecular regulation of N assimilation in Brassica napus, one of the most important oil crops worldwide. Here, we carried out a comprehensive genome-wide analysis of the N assimilation related genes (NAGs) in B. napus. A total of 67 NAGs were identified encoding major enzymes involved in N assimilation, including asparagine synthetase (AS), glutamate dehydrogenase (GDH), glutamine oxoglutarate aminotransferase (GOGAT), gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…4), which is a known N-responsive element in other plants (Lea et al 2007;Konishi and Yanagisawa 2010). In addition, presence of MYC, G-Box, GATA-motif is also reported to be N-responsive in different plants (Witko 2003;Konishi and Yanagisawa 2013;Zhang et al 2015;He et al 2021;Islam et al 2021). Though there is no report on N-responsive elements in wheat genes, this analysis confirms N-responsive of the above elements in wheat.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…4), which is a known N-responsive element in other plants (Lea et al 2007;Konishi and Yanagisawa 2010). In addition, presence of MYC, G-Box, GATA-motif is also reported to be N-responsive in different plants (Witko 2003;Konishi and Yanagisawa 2013;Zhang et al 2015;He et al 2021;Islam et al 2021). Though there is no report on N-responsive elements in wheat genes, this analysis confirms N-responsive of the above elements in wheat.…”
Section: Discussionsupporting
confidence: 62%
“…However, the list of these N-responsive elements in NR gene may not be complete and comprehensive, as there are still gaps in the reference genome sequence. Presence of these N-responsive elements are occurring in combination with the phytohormoneresponsive elements in the promoter region indicates the complex regulatory network between the N assimilation and hormonal pathways (He et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…According to KEGG pathway enrichment analysis, the DEGs associated with drought stress were assigned to phenylalanine biosynthesis ( ANTHOCYANIDIN REDUCTASE ) at the beginning of the phenylalanine metabolic pathway, in which phenylalanine ammonia lyase (PAL) acts not only as the rate‐limiting enzyme, but also as the key enzyme in response to drought, salt, and cold stress (Savoi et al, 2016). Studies show that amino acid metabolism in plants, as the precursor of many metabolites, has multiple functions in plant growth and stress responses (Ding, 2021; Thomas et al, 2008). In terms of tolerance to drought stress (Mostafa & Wang, 2020; Zhang et al, 2022c, d), nitrogen metabolism plays a non‐negligible role in resistance to drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Met is a precursor for the synthesis of ethylene, polyamines, and glucosinolates, and Met is converted to glycine to regulate seed development. Additionally, metabolites improve the ability of plants to resist abiotic stress (Di et al, 2002; Ding, 2021; Lu et al, 2011; Thomas et al, 2008). At the same time, it was found that the amino acid mixture improved the morphology and biochemical parameters, reduced the salt damage and increased the yield of broad bean (Abdelhamid et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The GS , GOGAT , and NR gene families have been studied in other plant species, like rice, pecan, and rapeseed ( He et al, 2021 ; Li et al, 2022 ; Qiao et al, 2023 ), a comprehensive genome-wide analysis of these gene families in soybean is still lacking. This study aims to fill this gap by identifying and analyzing these gene families in six legume species: Glycine max , Cicer arietinum , Lotus japonicus , Phaseolus lunatus , Phaseolus vulgaris , and Vigna unguiculata , with chromosome numbers of 20, 8, 6, 11, 11, and 11, respectively.…”
Section: Introductionmentioning
confidence: 99%